Pengaruh Terapi Oksigen Hiperbarik terhadap kadar Vascular Endothelial Growth Factor (VEGF) pada pasien Ulkus Diabetik - MR Akbar; RWM Kaligis; M Kasim (Jurnal Kardiologi Indonesia, 2007)
Background. Hyperbaric oxygen therapy (HBOT) increase endothelial oxygenation and stimulates vascular endothelial growth factor(VEGF) as the most specific and potent growth factor for angiogenesis, and increases wound healing process. The aim of the study is to know if five days HBOT can increase the level of VEGF in diabetic ulcer patients. Methods and results. Clinical experimental study was conducted on 12 diabetic ulcer patients who received HBOT 30 minutes, 3 times a day for 5 days (HBOT group) and 10 diabetic ulcer patients as a control group who did not receive HBOT (non-HBOT group). The VEGF level in both groups was measured on days 1 and 5. In HBOT group the mean level of VEGF on day 1 was 1241.325 + 237.6533 pg/ml and became 1244.458 + 264.5641 pg/ml (p = 0.583) on day 5, while in non-HBOT group the mean level of VEGF on day 1 was 1262.350 + 227.9603 pg/ml and became 1112.460 + 220.3795 pg/ml (p = 0.093) on day 5. There were no signifi-cant differentiation of VEGF level between HBOT group and non-HBOT group both on day 1 (p = 1) and day 5 (p = 0.872) Conclusions. Hyperbaric oxygen therapy for 5 days did not increase the VEGF level of diabetic ulcer patients.